Exploring how hospital based green spaces support stroke rehabilitation: A mixed methods multiple case study protocol - Louisa-Jane Burton; Tom Crocker; Peter Coventry; Liz Hill; Anna Walsh; Emma Myers; Michael Speed; Joseph Akanuwe; Anne Forster (PLoS ONE, 2026)
Background In-patient treatment and rehabilitation after stroke represent an important period for recovery, yet recommended levels of rehabilitation activity are challenging to achieve, and many patients remain inactive and at risk of low mood. Research in other conditions suggests that the use of green spaces can benefit in-patients, providing opportunities for activity and social interaction, and improving mood and wellbeing. However, little is known about the use of green spaces post-stroke. Aim To explore how, for whom, and under what conditions hospital based green spaces influence recovery, wellbeing and engagement with rehabilitation among stroke in-patients. Methods A mixed-method multiple case study will involve three hospital sites with different types of green spaces including those used for therapy, those newly designed for stroke survivors, and long-established spaces. Data collection will include gathering of contextual data (documentary analysis, mapping of the green space, interviews with green space designers and informal survey) to understand the setting, design, rationale, and maintenance; behavioural mapping (10-day period, two seasons per site) to understand usage; and semi-structured interviews with 45 in-patients and their visitors (including those who have and have not used the green space) and 30 multidisciplinary staff, to understand their experiences. Interview data will be analysed using the Framework approach. Mixed methods data will be integrated within and across cases to develop and refine a programme theory explaining how green space could support stroke recovery and wellbeing. Programme theory will be refined by expert groups of stroke survivors, carers and staff in three other locations. Discussion This study will generate a transferable programme theory and context-sensitive recommendations to inform the design, implementation and evaluation of green space in stroke care. We will disseminate findings widely to relevant audiences to influence future policy and practice.